2016
DOI: 10.1007/s00421-016-3327-9
|View full text |Cite
|
Sign up to set email alerts
|

Submaximal exercise intensity modulates acute post-exercise heart rate variability

Abstract: Preceding exercise intensity has a graded effect on recovery HRV measures reflecting cardiac vagal activity, even after correcting for the underlying HR. The immediate recovery following exercise is a potentially useful period to investigate autonomic activity, as multiple levels of autonomic activity can be clearly differentiated between using HRV. When investigating post-exercise HRV it is critical to account for the relative exercise intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 39 publications
5
43
0
10
Order By: Relevance
“…In contrast, inspection of Figure 4 suggests that exercise intensity may elicit a more graded (rather than binary) effect on HRV recovery (at least during the first hour post-exercise). This latter interpretation is consistent with the findings of a recent study by this research group demonstrating a graded response following three different exercise intensities (Michael et al, 2016). …”
Section: Hrv During Post-exercise Recoverysupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, inspection of Figure 4 suggests that exercise intensity may elicit a more graded (rather than binary) effect on HRV recovery (at least during the first hour post-exercise). This latter interpretation is consistent with the findings of a recent study by this research group demonstrating a graded response following three different exercise intensities (Michael et al, 2016). …”
Section: Hrv During Post-exercise Recoverysupporting
confidence: 93%
“…In addition to different modalities being utilized between these studies, the duration for which participants exercised at each intensity varies greatly, such as 2 min (Tulppo et al, 1996; Martinmaki et al, 2008), 3 min (Tulppo et al, 1998, 1999; Hautala et al, 2003; Karapetian et al, 2012), 5 min (Radaelli et al, 1996), 8 min (Casties et al, 2006; Michael et al, 2016), 10 min (Martinmaki and Rusko, 2008) and 15 or more min (Yamamoto et al, 1991; Saito and Nakamura, 1995; Leicht et al, 2008; Boettger et al, 2010). Nevertheless, an analysis of the literature allows us to identify some general responses for some HRV measures as a function of exercise intensity.…”
Section: Hrv During Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…While no correlations were found between the parasympathetic reactivation indices and mean HR, LnRMSSD 5‐10 minutes was positively correlated with the time spent in the low‐intensity zone (HR Z1) and negatively correlated with the time spent in the high‐intensity zone (HR Z3). Thus, it could be hypothesized that parasympathetic reactivation is correlated with the intensity of a previous exercise . Our results showed the presence of significant physiological stress (ie, HR and BF), especially during the last task ( mannequin ).…”
Section: Discussionmentioning
confidence: 55%
“…Thus, it could be hypothesized that parasympathetic reactivation is correlated with the intensity of a previous exercise. 13,35 Our results showed the presence of significant physiological stress (ie, HR and BF), especially during the last task (mannequin). Von Heimburg et al 5 reported that after having rescued six victims, the firefighters' blood lactate concentration reaches 13 mmol/L.…”
mentioning
confidence: 66%